2020
DOI: 10.2147/cmar.s241815
|View full text |Cite
|
Sign up to set email alerts
|

<p>Qualitative Evaluation of Virtual Touch Imaging Quantification: A Simple and Useful Method in the Diagnosis of Breast Lesions</p>

Abstract: Objective: To test the value of qualitative virtual touch imaging quantification (VTIQ) features in differentiating benign from malignant breast lesions. Methods: From November 2016 to August 2017, 230 lesions were subjected to conventional US and virtual touch imaging quantification before biopsy. The maximum shear wave velocity (SWVmax) was measured using a standardized method. Qualitative VTIQ features, including the "stiff rim" sign and color pattern classification, were assessed according to a binary clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…In these studies, the cutoff values for velocity in distinguishing benign from malignant lesions were reported as 3.2 to 5.1 m/s. [27][28][29][30] Our study affirmed similar results. We obtained the maximum velocity value for each lesion and found that the velocity value was significantly higher in malignant lesions (P < 0.0001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In these studies, the cutoff values for velocity in distinguishing benign from malignant lesions were reported as 3.2 to 5.1 m/s. [27][28][29][30] Our study affirmed similar results. We obtained the maximum velocity value for each lesion and found that the velocity value was significantly higher in malignant lesions (P < 0.0001).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies examine the utility of velocity, one of the quantitative parameters obtained by SWE, in differentiating malignant and benign breast lesions. In these studies, the cutoff values for velocity in distinguishing benign from malignant lesions were reported as 3.2 to 5.1 m/s 27–30 . Our study affirmed similar results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previously, multiple studies have been done to see the SWE role in detecting elasticity of liver, breast, thyroid and lymph nodes (LNs). 3 There are few studies that have been reported in placental tissue assessment. 4 There are limited studies available regarding placental elasticity using SWE worldwide and only 2-3 studies have been conducted in Pakistan to date.…”
Section: Introductionmentioning
confidence: 99%